Peran Customer Service Terhadap Kepuasan Pelanggan Di Rumah Sakit X - Kristianto, Bagoes; Pradana, Dimas Shakti; Aryani, Eka Yeni; Pandiangan, Stefani (Jurnal Sains Farmasi Dan Kesehatan, 2024)
Implementation of Customer Service in Hospital X is important in healthcare in Indonesia. Hospitals must provide quality, non-discriminatory and fair services through innovation and information technology. Thus, the purpose of this journal article is to find out how the role of Customer Service in serving Customers in hospitals that generates customer satisfaction with the services provided. This scientific work uses a qualitative research method which is an approach to generating data collected through observations, interviews, documentation and census data. This research method uses the understanding of social phenomena through the study of literature, the collection of information from laws, textbooks, newspapers and scientific journals. Thus, the results of this study show how the role of Customer Service in customer satisfaction in Hospital X.